Modelling the economic and environmental impacts of water resources in the context of climate neutrality in the EUSDR member states - Ionescu, Romeo Victor; Zlati, Monica Laura; Antohi, Valentin Marian; Cristea, Dragoș Sebastian; Petrea, Ștefan Mihai; Forțea, Costinela (Frontiers in Environmental Science, 2024)
Introduction This study explores the economic and environmental impacts of water resources in the context of achieving climate neutrality in the EU Strategy for the Danube Region (EUSDR). The research is focused on eight EUSDR member states: Bulgaria, Czechia, Germany, Croatia, Hungary, Austria, Romania, and Slovakia, with the aim of analyzing the dynamic relationship between water resources, economic growth, and environmental sustainability. Given the ambitious goals of the European Green Deal, this study examines how water management can support the transition towards climate neutrality. Methods A dynamic econometric model was developed using a consolidated database of relevant climate neutrality indicators from 2010 to 2021. The selected indicators included GDP per capita, water use in agriculture, gross water abstraction, sewage sludge production, and water productivity. The econometric model was validated using statistical tools such as the One-Sample Kolmogorov-Smirnov Test, and analysis was conducted using Gretl and IBM-SPSS 25 software. Results The findings reveal that water resources management significantly contributes to the achievement of climate neutrality targets. The model achieved over 86% significance in explaining the financial efforts needed to achieve the Green Deal’s 2030 and 2050 goals. Moreover, water productivity and investments in water-related infrastructure were found to play critical roles in ensuring the success of these climate policies. Discussion The results highlight the importance of policy coordination across the EUSDR member states and the need for increased investment in sustainable water resource management. Achieving climate neutrality requires addressing economic disparities between states and enhancing regional cooperation. Conclusion The proposed dynamic model offers a valuable tool for monitoring progress towards climate neutrality, particularly in relation to water resource management. This research underlines the need for targeted policy interventions and investments to meet the Green Deal’s goals while safeguarding the region's water resources.